Resurrection of Grammostola australis (Araneae: Theraphosidae) after seven decades: integrating molecular data, morphology, and distribution - Nicoletta, Micaela Mariel (2025)
The name Grammostola australis Gerschman et Schiapelli, 1948, syn. resurr. is herein resurrected from synonymy with G. inermis Mello-Leitão, 1941, based on morphological and molecular evidence. The holotypes of both species are redescribed, and the female of G. australis is described for the first time. Diagnoses of these species are also provided. Phylogenetic analyses recovered G. inermis as a distinct lineage from G. australis, suggesting that both species are more closely related to Brazilian and Uruguayan species of the genus Grammostola Simon, 1892, than to other Argentinean species. Similarly, Chilean species appear distinct from other Grammostola species, indicating that the Andes act as a geographical barrier.